The Influence of Viral Marketing, E-Trust, and Social Media Marketing on Purchasing Interest Mediated by Customer Satisfaction on Skintific Products - Muhammad Aldwin Daniswara Thamrin; Zulfitri, Zulfitri (Jurnal Multidisiplin Sahombu, 2025)
This study aims to determine the effect of viral marketing, e-trust and social media marketing on purchase intention mediated by customer satisfaction (a study on scientific products in West Jakarta). The research was conducted on 130 respondents with 150 tabulated answers using a quantitative approach. The research model used is Structural Equation Model (SEM). The results of the study indicate that viral marketing does not affect customer satisfaction, e-trust affects customer satisfaction, social media marketing does not affect customer satisfaction, customer satisfaction affects purchase intention, customer satisfaction does not mediate between viral marketing and purchase intention, customer satisfaction mediates between e-trust and purchase intention, customer satisfaction does not mediate between social media marketing and purchase intention.